PEMBELAJARAN DI SEKOLAH DASAR BERBASIS PADA PERTUMBUHAN DAN PERKEMBANGAN PESERTA DIDIK - Ujang jamaludin (JPsd (Jurnal Pendidikan Sekolah Dasar), 2015)
The success of teachers in carrying out the task as educators in elementary schools is not enough to rely only high spirits, but must also have sufficient knowledge about the growth and development of learners, because of good teaching should be based on the growth and development of learners, if this is done then the process more effective and efficient learning. Under these conditions, it is necessary educators to understand more deeply about it. Growth and development can not be separated, meaning that there will be no development if the child is not growing. Term growth is associated with changes in the form of biological / physical, while the developments related to the change in function biolgis / physical human being in line with its growth. In general, human growth and development and the growth and development each have specific characteristics, such as growth and development of elementary school students. Factors affecting the growth and development of learners Elementary School is Descendants (heredity) and the environment (family environment, school environment, peer groups and communities) The potential default on students is very likely to be developed through the learning process. Keywords: Growth, development, educators, elementary school students